PEMENANGAN PASANGAN PRABOWO-HATTA MELALUI BASIS MASSA DALAM PEMILIHAN PRESDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA DI KOTA PEKANBARU TAHUN 2014 - Herianti, Septia; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The elections of President and Vice President of the Republic of Indonesia in 2014 was the third elections were held by vote directly. There’s only two pairs of candidates compete in the elections of President and Vice President of the Republic of Indonesia in 2014, number 1 Prabowo-Hatta and Jokowi-JK with number 2. Although the results of the presidential elections in 2014 was won by Jokowi-JK, Prabowo-Hatta managed to dominate the vote in twelve districts in the Pekanbaru City with the acquisition of 261.593 votes or 67% . This shows that the winning team of Prabowo-Hatta secured the support of the masses. The problem of this research is how the winning Prabowo-Hatta through the mass bases in the elections of president and vice president of the Republic Indonesia in the city of Pekanbaru in 2014.This study aims to look at the winnings of Prabowo-Hatta through a mass bases in the elections of President and Vice President of the Republic of Indonesia in 2014 conducted by team of Koalisi Merah Putih in Pekanbaru using three approaches in political marketing that is pull marketing, push marketing and pass marketing. This study use a qualitative approach and descriptive research with data collection techniques is interview and documentation.The results showed that the winning of Prabowo-Hatta through a mass bases in the elections of President and Vice President of the Republic of Indonesia in Pekanbaru City in 2014 was through the mass bases of the party cadres from Koalisi Merah Putih, the wings of the party, community leaders, community organizations and volunteers by offering products via paid media and without paying (pull marketing), disseminating the program to the community candidate (push marketing), and make the community leaders, community organizations and volunteers as an influencer (pass marketing) .Keywords : Elections of the President, Base Masses, Political Marketing